Prospective associations between early long-term household tobacco smoke exposure and antisocial behaviour in later childhood. Issue 7 (21st May 2013) - Pagani, Linda S; Fitzpatrick, Caroline
Abstract : Background: Using a prospective birth cohort design, we estimate the relative contribution of long-term postnatal nicotine exposure from 17 to 86 months on children's subsequent antisocial behaviour by the end of fourth grade. Method: Parents reported the amount of household smoke exposure (at 17, 41, 65 and 86 months) for all 2055 children from the Quebec Longitudinal Study of Child Development. Main outcome measures include teacher- and child-reported antisocial and physically aggressive behaviour (at 121 months). Results: In terms of prevalence, 58% of parents reported that their children were never exposed to secondhand smoke in the home, while 34% and 8% of parents reported transient and continuous levels of secondhand smoke, respectively. When compared with never exposed children, children exposed to continuous secondhand smoke scored higher on self-reported aggressive behaviour and teacher-rated antisocial behaviour in fourth grade, B=0.336 (95% CI 0.155 to 0.517) and B=0.319 (95% CI 0.107 to 0.531), respectively. Similarly, children exposed to transient levels of secondhand smoke scored higher on aggressive and antisocial behaviour, B=0.714 (95% CI 0.456 to 0.972) and B=0.566 (95% CI 0.260 to 0.872), respectively. Conclusions: The observed prevalence is concordant with worldwide estimates of children's exposure to secondhand smoke. In comparison with their never exposed peers, children continuously and intermittently exposed to secondhand smoke in childhood showed an increased propensity toward physical aggression and antisocial behaviour by the end of fourth grade. We found no evidence of dose-dependence.